ChemInform Abstract: Chiral Phosphoric Acid‐Catalyzed Enantioselective Three‐ Component Aza‐Diels—Alder Reactions of Aminopyrroles and Aminopyrazoles. Issue 45 (23rd October 2014) - Brioche, Julien; Courant, Thibaut; Alcaraz, Lilian; Stocks, Michael; Furber, Mark; Zhu, Jieping; Masson, Geraldine
Abstract The developed Povarov reaction proceeds with high enantioselectivity and high diastereoselectivity.